2015
DOI: 10.1186/s12871-015-0039-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of clinical performance of guardian laryngeal mask with laryngeal mask airway ProSeal

Abstract: BackgroundThe Guardian Laryngeal Mask Airway (G-LMA) is a new silicone-based single-use extraglottic device with the drainage port and a cuff pilot valve with pressure indicator. The aim of this study is to compare the clinical performance of this laryngeal mask airway with ProSeal laryngeal mask airway (P-LMA).MethodsIn this prospective randomized study, we included adult patients with ASA grading I and II scheduled for elective surgery requiring supine position under total intravenous anesthesia. The patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…The presence of blood on the device upon removal of a SGA often indicates minor trauma associated with device insertion. The reported incidence of this for the cLMA is between 12 and 15% [ 55 ] and 9 and 22% in association with the PLMA [ 56 , 57 ], depending on insertion technique. An incidence of blood staining of 20% has been described with the Guardian CPV laryngeal mask [ 57 ].…”
Section: Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of blood on the device upon removal of a SGA often indicates minor trauma associated with device insertion. The reported incidence of this for the cLMA is between 12 and 15% [ 55 ] and 9 and 22% in association with the PLMA [ 56 , 57 ], depending on insertion technique. An incidence of blood staining of 20% has been described with the Guardian CPV laryngeal mask [ 57 ].…”
Section: Complicationsmentioning
confidence: 99%
“…The reported incidence of this for the cLMA is between 12 and 15% [ 55 ] and 9 and 22% in association with the PLMA [ 56 , 57 ], depending on insertion technique. An incidence of blood staining of 20% has been described with the Guardian CPV laryngeal mask [ 57 ]. The typical incidence of blood on the i-gel at removal is between 4% and 13% [ 58 60 ] but has been reported to be as high as 20%, albeit in novice users [ 61 ].…”
Section: Complicationsmentioning
confidence: 99%
“…Some limitations of this study include all patients being female and paralyzed, and all insertions having been performed by one of two consultant anesthetists experienced in the use of both models. The subsequent 2015 study by Pajiyar et al showed 95% success rates of Guardian insertion with an insignificant difference to rates of Proseal insertion (n=40 each, p>0.05) with slightly superior OLP (32 vs. 29 cmH 2 O, p<0.05) [11]. Limitations of this subsequent study were similar, with all patients being female and paralyzed.…”
Section: Context Of This Studymentioning
confidence: 77%
“…The existing literature for the Guardian LMA reports 100% success rate. [10,11] Using G * Power [12], a sample size of at least 50 was needed to identify a statistically-significant difference (one-tailed, α=0.05, β=0.80) from an expected success rate of 95% to an actual success rate of 80%.…”
Section: Sample Collectionmentioning
confidence: 99%
“…The pilot balloon valve with pressure logo indicates visual intracuff pressure (Yellow <40 cmH2O, Green 40-60 cmH2O and Red >60 cmH2O) ( Figure 10). A study suggests that it provides sealing pressures as high as 32 cm H2o [72,73].…”
Section: The Lma Guardian™ (Glma)mentioning
confidence: 99%